CROSSROADS OF WAR: THE PEOPLE OF NKANDLA IN THE ZULU REBELLION OF 1906 - Thompson, Paul S. (Scientia Militaria - South African Journal of Military Studies, 2011)
The rebellion and Nkandla The Zulu Rebellion of 1906 was the violent response to the imposition of a poll tax of £1 on all adult males (with exempted categories) by the government of the British South African colony of Natal on the part of a section of the indigenous, Zulu-speaking people. The rebellion was in the nature of “secondary resistance” to European colonization, and the poll tax was only the immediate cause of it. Not all the African people (who made up 82% of the colony’s population) participated in the rebellion; only a few did, but there was the potential for a mass uprising, which inspired great fear among the European settlers (who made up just 8,3% of the population) and prompted the colony’s responsible government to take quick and vigorous action to crush the rebellion before it could spread. The object of the rebels, beyond the removal of the poll tax, was to drive the white settlers out of the country and to restore the pre-colonial regime, although it was unclear just what they thought that might have been. In the case of most (but not all) of the those living in the Province of Zululand, i.e. the northeastern quarter of the Colony of Natal, it meant the restoration of the Zulu monarchy under the chief Dinuzulu.